Immune-microbiota dysregulation in maintenance hemodialysis: a 16S rRNA sequencing-based analysis of gut flora and T cell profiles - Yan Lv; Xiuting Yang; Xiaowu Sun; Xiaohong Ren (Renal Failure)
Background Maintenance hemodialysis (MHD) patients frequently exhibit immune dysregulation and gut dysbiosis, both of which contribute to increased infection risk and adverse outcomes. However, the relationship between gut microbial composition and immune competence in this population remains underexplored.Methods This study assessed 45 MHD patients and 30 healthy controls, stratifying MHD patients into immunocompetent (HD-NLI, CD4+/CD8+ ≥ 1) and immunodeficient (HD-LI, CD4+/CD8+ < 1) groups. Circulating cytokines (IL-6, IL-10, IL-12, TNF-α, IFN-γ) were quantified using ELISA. Gut microbiota profiles were derived via 16S rRNA gene sequencing (V3-V4 regions), followed by QIIME2 and LEfSe-based bioinformatics analyses.Results HD-LI patients displayed severe T cell dysregulation and elevated pro-inflammatory cytokines. Compared to controls, HD patients had reduced abundance of beneficial taxa (e.g., Prevotella copri, Bacteroides vulgatus, Agathobacter), and enrichment of pro-inflammatory taxa (e.g., Escherichia-Shigella, Blautia, Citrobacter). LEfSe identified 39 discriminatory taxa with distinct immune group signatures. Redundancy analysis revealed that CD4+ levels, CD4+/CD8+ ratios, and TNF-α significantly shaped microbiota composition. Correlation analysis confirmed strong associations between immune parameters and microbial taxa involved in short-chain fatty acid (SCFA) metabolism.Conclusion This study provides novel evidence linking gut microbial dysbiosis to immune impairment in MHD patients. The findings suggest that SCFA-producing bacteria are depleted in immunodeficient states, offering a potential target for microbiota-directed immunomodulatory therapies in ESRD.